AN ALGEBRAIC MODEL FOR WORKING CAPITAL. - Jennings, Robert M. (The Accounting Review, 1960)
Abstract The article presents an algebraic model for working capital. The balance sheet equation in slightly expanded form can be utilized algebraically to demonstrate all the potential increases or decreases in working capital. There are four mathematical equations to demonstrate these changes in balance sheet. The first mathematical equation is asset is equal to the sum of liability and owner's equity. The second equation is that sum of the values of current assets and fixed assets is equal to sum of current liabilities, fixed liabilities and owner's equity. The third equation is that difference in current assets and current liabilities is equal to the difference of the sum of fixed liabilities and owner's equity with fixed assets. The fourth equation is the working capital is equal to the difference in sum of fixed liabilities and owner's equity with fixed assets. Fourth equation defines working capital in terms of three general classifications of accounts and actually equates working capital to their algebraic sum.